Reproducible and relocatable regional ocean modelling: fundamentals and practices - J. Polton; J. Harle; J. Holt; A. Katavouta; D. Partridge; J. Jardine; S. Wakelin; J. Rulent; A. Wise; K. Hutchinson; D. Byrne; D. Bruciaferri; et al. (Geoscientific Model Development, 2023)
In response to an increasing demand for bespoke or tailored regional ocean modelling configurations, we outline fundamental principles and practices that can expedite the process to generate new configurations. The paper develops the principle of reproducibility and advocates adherence by presenting benefits to the community and user. The elements of this principle are reproducible workflows and standardised assessment, with additional effort over existing working practices being balanced against the added value generated. The paper then decomposes the complex build process, for a new regional ocean configuration, into stages and presents guidance, advice and insight for each component. This advice is compiled from across the NEMO (Nucleus for European Modelling of the Ocean) user community and sets out principles and practises that encompass regional ocean modelling with any model. With detailed and region-specific worked examples in Sects. 3 and 4, the linked companion repositories and DOIs all target NEMOv4. The aim of this review and perspective paper is to broaden the user community skill base and to accelerate development of new configurations in order to increase the time available for exploiting the configurations.